Electrosprayed poly(lactic-co-glycolic acid) particles as a promising drug delivery system for the novel JNK inhibitor IQ-1; European Polymer Journal; Vol. 127 - Kibler E. V. Elina Vitaljevna; Lavrinenko A. K. Anastasiya Konstantinovna; Kolesnik I. M. Iljya Maksimovich; Stankevich K. S. Ksenia Sergeevna; Bolbasov E. N. Evgeny Nikolaevich; Kudryavtseva V. L. Valeriya Lvovna; Leonov A. A. Andrey Andreevich; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Khlebnikov A. I. Andrey Ivanovich; Quinn M. T. Mark; Tverdokhlebov S. I. Sergei Ivanovich (2020, 2020)
Title screen